Laser Pan-Retinal Photocoagulation to Treat Central Retinal Vein Occlusion - Roland Iqbal; AK Ansyori; Ramzi Amin (Sriwijaya Journal of Ophthalmology, 2019)
Introduction. Retinal Vein Occlusion (RVO) is the second most common retinal blood vessel disease after diabetic retinopathy. CRVO is an acute blockage of the central retinal vein that causes abnormalities in the retina, characterized by sudden decreased vision. Based on the potential for vision loss from this retinal disease, proper diagnosis and management is needed to prevent further complications. Case Presentation. A man, age 50 years old, a civil servant, came to the eye clinic of Mohammad Hosein Hospital on February 2017. The main complaint was vision of right eye suddenly blurred since 5 months before. Based on the above examination found decreased vision in one eye, with visual acuity better than 6/60 and no RAPD. The funduscopic examination above shows the presence of dilatation and tortousity in the central retinal vein, dot / blot bleeding and flame shaped hemorrhages in all quadrants, exudates, neovascularization of the retina and optic disk, and the presence of edema in the optic disc and macula. Conclusion. Management performed on these patients is by performing a Pan-Retinal Photocoagulation (PRP) laser and Grid-Pattern Photocoagulation. The selection of this therapy is based on the consideration that the patient has been suffering from CRVO for more than 3 months.